2021
DOI: 10.1177/00220345211029185
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Osteoinductive Implant Surface Using Layer-by-Layer Assembly

Abstract: Osseointegration of dental, craniofacial, and orthopedic implants is critical for their long-term success. Multifunctional surface treatment of implants was found to significantly improve cell adhesion and induce osteogenic differentiation of dental-derived stem cells in vitro. Moreover, local and sustained release of antibiotics via nanolayers from the surface of implants can present unparalleled therapeutic benefits in implant dentistry. Here, we present a layer-by-layer surface treatment of titanium implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…that form polyelectrolyte multilayers. LBL assembly can also be used to incorporate BMPs for osseointegration of Ti implants. However, the process of LBL assembly is too slow, and growth factor incorporated implants need appropriate cold storage and shipping making LBL coating of implants highly cost ineffective.…”
Section: Hard and Soft Tissue Integration Around Percutaneous Bone-an...mentioning
confidence: 99%
“…that form polyelectrolyte multilayers. LBL assembly can also be used to incorporate BMPs for osseointegration of Ti implants. However, the process of LBL assembly is too slow, and growth factor incorporated implants need appropriate cold storage and shipping making LBL coating of implants highly cost ineffective.…”
Section: Hard and Soft Tissue Integration Around Percutaneous Bone-an...mentioning
confidence: 99%
“…LBL self-assembly : LBL self-assembly is a surface modification method based on the alternating assembly of oppositely charged polyelectrolytes to fabricate multilayer coatings [ 53 , 54 ]. This method is easy to control the thickness of coatings but also can release drugs layer by layer to promote osseointegration [ 55 ].…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…Gent has shown excellent antibacterial activity for most Gram-negative bacteria because it can block the protein synthesis of bacteria by binding to the ribosome of the virus. Thus, Gent is also often used to improve implant osseointegration by enhancing the antimicrobial capacity of implants [ 53 , 80 ]. For instance, Yang et al found that Gent-loaded TNTs achieved desirable osseointegration in the rat model by significantly inhibiting the growth of bacteria and implant-associated infections [ 81 ].…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…Early studies focus on the treatment to enhance the bioactivity of the implant surface, for example, surface modification, [ 5 ] dosing antibiotics, [ 6 ] and loading active ingredients, such as gold nanoparticles. [ 7 ] Recent approaches have focused on simultaneously improving the surface biological activity and antibacterial performance of implants.…”
Section: Introductionmentioning
confidence: 99%